2008
DOI: 10.2174/187152008784220311
|View full text |Cite
|
Sign up to set email alerts
|

Polynucleotide Kinase as a Potential Target for Enhancing Cytotoxicity by Ionizing Radiation and Topoisomerase I Inhibitors

Abstract: The cytotoxicity of many antineoplastic agents is due to their capacity to damage DNA and there is evidence indicating that DNA repair contributes to the cellular resistance to such agents. DNA strand breaks constitute a significant proportion of the lesions generated by a broad range of genotoxic agents, either directly, or during the course of DNA repair. Strand breaks that are caused by many agents including ionizing radiation, topoisomerase I inhibitors, and DNA repair glycosylases such as NEIL1 and NEIL2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 86 publications
0
24
0
Order By: Relevance
“…Phage T4 polynucleotide kinase and hPNKP share similar nucleic acid kinase and phosphatase activities. However, with the exception of the enzyme active sites, the proteins bear no recognizable homology (26,28). The phosphatase domains of both proteins belong to the haloacid dehalogenase superfamily (26,39,40) with a conserved DxDGT motif, where the first Asp forms a covalent phospho-aspartate intermediate with the substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phage T4 polynucleotide kinase and hPNKP share similar nucleic acid kinase and phosphatase activities. However, with the exception of the enzyme active sites, the proteins bear no recognizable homology (26,28). The phosphatase domains of both proteins belong to the haloacid dehalogenase superfamily (26,39,40) with a conserved DxDGT motif, where the first Asp forms a covalent phospho-aspartate intermediate with the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that PNKP could be a potential target for small molecule inhibitors (2,28). We report here the development of a fluorescence-based assay for screening chemical libraries for inhibitors of the phosphatase activity of PNKP and its application in the screening of a library of drug-like polysubstituted piperidines.…”
Section: Introductionmentioning
confidence: 99%
“…Substrate binding was stabilized by mutation of Asp170 to alanine (PNKP D170A ). Asp170 is predicted to attack the 3′-phosphate, generating a covalent phosphoaspartate intermediate in the first step of the reaction (13). We were successful in crystallizing this domain in the apo form, and bound to five nucleotide single-stranded DNAs bearing either C, T, or A at the 3′ position, and these structures were determined to resolutions between 1.7 and 2.1 Å (Table S1, Materials and Methods, and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The PNKP phosphatase domain adopts a haloacid dehydrogenase (HAD) fold (14) commonly found in many phosphatases, and contains conserved active site residues that suggest the enzyme utilizes a two step mechanism that is characteristic of this family (13). Key to catalysis is an active site Mg þþ ion, which binds and stabilizes the growing negative charge on the substrate phosphate during catalysis, as well as binding and positioning one of the critical active site aspartate residues.…”
Section: Resultsmentioning
confidence: 99%
“…This stage of processing in the repair by NHEJ is believed to be responsible for errors resulting from losses and additions of nucleotides at the sites of DNA DSB rejoining (Mahaney et al, 2009;Lieber, 2010). In the processing of broken DNA ends, the following enzymes are involved: the nuclease Artemis (Yannone et al, 2008), the DNA polymerases of the family X (Pol and Pol ) (Moon et al, 2007), and the terminal deoxynucleotidyl transferase (Mahaney et al, 2009), as well as polynucleotide kinase having both the kinase and phosphatase activities (Bernstein et al, 2008). Also, some other substances participate in the process, such as aprataxin (APTX) which catalyzes the removal of AMP groups at the 5 'ends of the DSB (Rass et al, 2008), the PALF-factor, and the protein cernunnos (XLF), which interact with XRCC4 in the activation of the DNA-ligase complex XRCC4/DNK-ligase IV/XLF Yano et al, 2009).…”
Section: Repair Of Dna Double Strand Breaksmentioning
confidence: 99%